Melatonin versus midazolam premedication in children undergoing surgery: A pilot study. (29th October 2015) - Gitto, Eloisa; Marseglia, Lucia; D'Angelo, Gabriella; Manti, Sara; Crisafi, Caterina; Montalto, Angela Simona; Impellizzeri, Pietro; Reiter, Russel J; Romeo, Carmelo
Abstract : Aim: Melatonin has been proposed as a premedication alternative to midazolam, preceding anaesthesia induction. However, to our knowledge, data concerning interaction between melatonin and intravenous anaesthetic drugs in children are not available. The aim of this prospective, randomized, double‐blind pilot study was to investigate the possible effect of melatonin premedication, in comparison to midazolam, on the required infusion of propofol in children undergoing surgery. As a secondary outcome, the effect of oral melatonin on the preoperative sedation level and on the post anaesthesia recovery score was evaluated. Methods: Children between the age of 5 and 14 years, scheduled for elective surgery, were prospectively enrolled between January 2012 and December 2013, and randomly assigned to two groups based on whether they received oral melatonin (0.5 mg/kg) or oral midazolam (0.5 mg/kg) premedication before induction of anaesthesia with propofol. Degree of sedation before and after anaesthesia was also evaluated. Results: Ninety‐two patients were studied, 46 for each group. We found that oral administration of melatonin significantly reduced doses of propofol required for induction of anaesthesia in paediatric patients, more than midazolam ( P < 0.001). No statistically significant differences were found in the pre‐ and post‐anaesthesia sedation score ( P = 0.387 and P = 0.525, respectively) between the two groups. Conclusions: The present study demonstrates that melatonin enhances the potency of propofol also in paediatric patients. Moreover, considering the paediatric level of sedation, melatonin was equally as effective as midazolam. These data support the use of melatonin as a premedicant in paediatric surgical patients.